2013
DOI: 10.1111/cas.12110
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of monocytes/macrophages with ovarian cancer cells promotes angiogenesis in vitro

Abstract: It has been established that macrophages and endothelial cells infiltrate peritoneum in the vicinity of tumor implants of epithelial ovarian cancer (EOC). This study investigates whether the interaction of ovarian cancer cells and tumor-associated macrophages could promote the involvement of endothelial cells in angiogenesis. Macrophage phenotypes were detected by fluorescence-activated cell sorting, and cytokine/chemokine secretion was measured by enzyme linked immunosorbent assay. The effect of co-culture of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(47 citation statements)
references
References 29 publications
3
43
0
Order By: Relevance
“…Our previous work suggested that the co-culture of tumor-associated macrophage supernatant with EOCs could promote endothelial cell migration [3]. Here, we further showed that exosomes secreted from TAMs in the absence of EOC stimulation could suppress the migration of endothelial cells.…”
Section: Resultssupporting
confidence: 62%
“…Our previous work suggested that the co-culture of tumor-associated macrophage supernatant with EOCs could promote endothelial cell migration [3]. Here, we further showed that exosomes secreted from TAMs in the absence of EOC stimulation could suppress the migration of endothelial cells.…”
Section: Resultssupporting
confidence: 62%
“…Increasing evidence has shown that the interactions between tumor cells and infiltrated macrophages create a tumor‐supportive microenvironment . High levels of POSTN accumulate in ascites from ovarian cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has shown that the interactions between tumor cells and infiltrated macrophages create a tumor-supportive microenvironment. 32,33 High levels of POSTN accumulate in ascites F I G U R E 5 THP-1-derived macrophages were recruited by periostin (POSTN) by A2780 cell conditioned medium (CM). A, Representative images of THP-1-derived macrophages (Mφ) migrating to A2780 cell-derived CM.…”
Section: Discussionmentioning
confidence: 99%
“…Also immune cells and mesenchymal cells can interact with malignant cells. Wang et al [41] showed that the cross talk between ovarian cancer cells and tumor-associated macrophages enhances the ability of endothelial cells to promote the progression of ovarian cancer. Moreover, Lis et al [42] demonstrated that co-culture of ovarian cancer cells in direct cellular contact with mesenchymal stem cells induces broad transcriptomic changes related to cellular adhesion, invasion, migration, proliferation and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%